PENGEMASAN BUDAYA LOKAL DALAM PROGRAM TELEVISI LOKAL (Studi Kasus Program Budaya âAdiluhungâ Pada Stasiun Televisi Lokal Yogyakarta âJogya TVâ) - , VERONIKA SETYADJI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Adiluhung Program is a program of which themes contain elements of the local culture i.e. peopleâs tradition and cultural heritage. In its development, this program can provide knowledge and information to all levels of society so they could know more closely with their local culture. Swift currents of globalization bring lack of respect for their own culture especially among the younger generation so that the local culture is starting to lose its existence. Entertainment programs aired by private television allow local television lost its luster